2021
DOI: 10.1182/blood.2020009396
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus-specific T-cell reconstitution following letermovir prophylaxis after hematopoietic cell transplantation

Abstract: Decreased cytomegalovirus (CMV)-specific immunity after hematopoietic cell transplantation (HCT) is associated with late CMV reactivation and increased mortality. Whether letermovir prophylaxis-associated reduction in viral exposure influences CMV-specific immune reconstitution is unknown. We compared polyfunctional CMV-specific T-cell responses in a prospective cohort of allogeneic HCT recipients who received letermovir to controls who received PCR-guided preemptive therapy prior to the introduction of leterm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 36 publications
(56 reference statements)
5
74
1
Order By: Relevance
“…12,13,20,21 A recent study of HCT recipients receiving letermovir (N 5 56, including 10 CBT who overlap with this study) vs historical controls (N 5 93, 1 CBT) demonstrated that day 190 polyfunctional CMV-specific T-cell responses were decreased in letermovir recipients, and increased CMV-specific T-cell polyfunctionality was associated with a lower risk of subsequent CS-CMVi. 14 These concepts are supported by our finding that none of the individuals with delayedonset CS-CMVi after letermovir discontinuation had CS-CMVi by day 198. Thus, monitoring CMV-specific immunity prior to stopping letermovir in CBT recipients may be important for risk-stratification.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…12,13,20,21 A recent study of HCT recipients receiving letermovir (N 5 56, including 10 CBT who overlap with this study) vs historical controls (N 5 93, 1 CBT) demonstrated that day 190 polyfunctional CMV-specific T-cell responses were decreased in letermovir recipients, and increased CMV-specific T-cell polyfunctionality was associated with a lower risk of subsequent CS-CMVi. 14 These concepts are supported by our finding that none of the individuals with delayedonset CS-CMVi after letermovir discontinuation had CS-CMVi by day 198. Thus, monitoring CMV-specific immunity prior to stopping letermovir in CBT recipients may be important for risk-stratification.…”
Section: Resultsmentioning
confidence: 60%
“…12 This phenomenon may be in part due to reduced CMV-specific immune reconstitution resulting from lack of exposure to CMV antigens. 13,14 CBT recipients may be at particularly increased risk for delayed-onset CMV given slower immune reconstitution compared with other cell sources. [15][16][17] The efficacy of letermovir for CMV prophylaxis after CBT is not well described, and few were included in the phase 3 trial.…”
Section: Introductionmentioning
confidence: 99%
“…A major obstacle in management of HCMV reactivation post-HSCT is potential antiviral drug-related toxicities from ganciclovir and foscarnet. Prophylaxis with safer agents such as Letermovir still carries a risk of viral resistance (Douglas et al, 2019), expense and the potential for delayed HCMV-specific T cell recovery (Zamora et al, 2021). Early discrimination of low-level and high-level reactivators could facilitate the tailoring of therapeutic decisions, as patients who develop self-limiting, low-level HCMV DNAemia may benefit from a shortened duration of prophylaxis or higher viral load threshold for pre-emptive therapy initiation.…”
Section: Discussionmentioning
confidence: 99%
“…The patients were selected based on the following criteria: 1) recipients were CMV seropositive; 2) donors were CMV seronegative, allowing us to track the naïve T cell response to CMV; 3) both donors and recipients expressed the HLA-A*02:01 allele, allowing us to identify CMV-specific CD8+ T cells using published TCR sequences and a p:MHC tetramer (epitope NLVPMVATV from CMV); and 4) CMV reactivation occurred between 30 and 90 days after transplant. Following nmHSCT, each of the four patients underwent regular peripheral blood draws and weekly CMV surveillance by PCR (24). Blood draws were used to assess white blood cell (WBC) counts and processed to cryopreserve peripheral blood mononuclear cells (PBMCs) (Figure 1B).…”
Section: Patient Cohort Sample Processing and Virology Datamentioning
confidence: 99%